Acute urachal cystitis in two children - Sarah Ellul; Adrienne Zerafa Simler; Mohamed Shoukry (Elsevier, 2022)
Introduction: Persistent Urachal cysts (UC) are rare congenital pathologies caused by failure of obliteration of urachal remnant. This can lead to potential morbidities including infection and fistula formation. Presentation of such pathology varies resulting in significant delay in diagnosis. This article reports mysterious presentations of UC in children investigated for non-specific abdominal pain. Case description: Two cases presented with worsening central abdominal pain associated with occasional vomiting for the previous 4-6 months.Physical examination of the girl revealed tenderness over peri-umbilical area with no palpable masses. She had normal white cell (WCC), neutrophil count and C-Reactive Protein (CRP). Her Ultrasound scan noted a cylindrical hypoechoic structure in keeping with a urachal cyst.However, the boy experienced lower abdominal tenderness with on masses felt and an elevated WCC and neutrophil count but normal CRP. USS reported a rounded, fibrosed lesion with a fibrosed tract, in keeping with non-complicated urachal remnant.Laparoscopic findings for first case, noted UC with a visible midline patent tract connecting to urinary bladder; such connection confirmed using injected saline. During the second case, the cystic structure, was connected to the umbilical stump. In both cases, both the UC and tract were dissected off and completely resected. Both had an uneventful post-operative recovery, with no further episodes of abdominal pain during follow-up appointments. Conclusion: Persistent UC could be easily mis-diagnosed with other commoner surgical abdominal pains. High suspicion, careful examination, and relevant radiological investigations, lead to earlier diagnosis and proper surgical management.